Feminisme R. A. Kartini dan Relevansinya Bagi Gereja Di Indonesia - Samuel Pella; Hendrikus Ance (Fakultas Teologi, Universitas Sanata Dharma, 2025)
Feminism has become an engaging and relevant topic in today’s era. The position and role of women in society are reasons why feminism continues to be advocated. This study discusses one of the feminist figures in Indonesia who fought in her way in her time. R.A. Kartini certainly had her uniqueness in advocating for women's rights, especially in obtaining education. The experiences and observations of social practices she encountered, both in Javanese culture and how the colonialists treated natives, were expressed in the form of writings (correspondence) with some of her friends in the Netherlands. Eleven years after her death, this collection of letters was published into a book titled “Habis Gelap Terbitlah Terang” (“Out of Dark Comes Light”). This book inspired many people, especially in Indonesian society, to believe that women also have an essential role in communal life. Kartini’s struggle for women’s equality opened people’s eyes to take action in addressing the social inequalities present in society. Previous studies have largely examined Kartini from the perspectives of educational and national emancipation, but few have explored her relevance to church life, particularly regarding the role of Catholic women. This study aims to examine Kartini’s feminist ideas and discover their relevance to the Indonesian Church through the work of the Indonesian Catholic Women's Association (WKRI). This study uses a qualitative method with a historical-theological approach, including a literature review of Kartin’s letters, Church documents, and a case study of the role of WKRI. The results of the study indicate that Kartini’s feminist ideas have inspired the empowerment of Catholic women and encouraged WKRI to become a vehicle for women's active participation in Church and community life. This study confirms that Kartini’s ideas remain relevant as a basis for theological reflection and praxis in the struggle for gender equality and social justice in the Indonesian Church.AbstrakFeminisme telah menjadi topik yang menarik dan relevan di era saat ini. Posisi dan peran perempuan dalam masyarakat menjadi alasan mengapa feminisme terus diperjuangkan. Kajian ini membahas salah satu tokoh feminis di Indonesia yang berjuang dengan caranya sendiri pada masanya. RA Kartini tentu memiliki keunikan dalam memperjuangkan hak-hak perempuan, khususnya dalam memperoleh pendidikan. Pengalaman dan pengamatan terhadap praktik-praktik sosial yang ditemuinya, baik dalam budaya Jawa maupun bagaimana penjajah memperlakukan penduduk asli, dituangkan dalam bentuk tulisan (surat-menyurat) dengan beberapa sahabatnya di Belanda. Sebelas tahun setelah kematiannya, kumpulan surat-surat ini diterbitkan menjadi sebuah buku berjudul “Habis Gelap Terbitlah Terang”. Buku ini menginspirasi banyak orang, khususnya di masyarakat Indonesia, untuk percaya bahwa perempuan juga memiliki peran penting dalam kehidupan bermasyarakat. Perjuangan Kartini untuk mengangkat harkat dan martabat perempuan membuka mata masyarakat untuk melakukan sesuatu terhadap ketimpangan sosial yang terjadi di masyarakat. Kondisi sosial tersebut mendorong Kartini untuk tidak berpaling dan membebaskan perempuan dari penindasan dan keterbelakangan sosial. Relevansi pemikiran Kartini dapat ditemukan dalam Wanita Katolik Republik Indonesia (WKRI) yang masih eksis hingga saat ini. Organisasi ini menjadi wadah bagi wanita Katolik untuk berpartisipasi dalam kehidupan bermasyarakat. Organisasi ini muncul dari keprihatinan sosial, khususnya isu upah rendah bagi perempuan dan keterbelakangan perempuan di berbagai bidang. Kartini meninggalkan pelajaran berharga bahwa ketidakadilan sosial menantang individu untuk tidak berdiam diri demi kebaikan bersama (bonum commune).